Contextual Procedures Framework of Career Plateauing among Accountants in the Health Insurance Organization: A Multi-Faceted Grounded Theory Approach - Deylami, Safiyeh; Matoufi, Alireza; Khozein, Ali; Garkaz, Mansour (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2026)
Objective: The present study aimed to develop a grounded theoretical model explaining the functional factors, contextual conditions, strategic responses, and consequences of career plateauing among accountants working in the Health Insurance Organization.Methods and Materials: This research adopted a qualitative exploratory design based on a multi-faceted grounded theory approach. The statistical population consisted of experienced financial managers and professional accountants employed within the Health Insurance Organization. Participants were selected using purposive and theoretical sampling to ensure rich experiential data. Data were collected through in-depth semi-structured interviews conducted during 2025, continuing until theoretical saturation was achieved. Data analysis followed systematic grounded theory procedures including open coding, focused coding, axial coding, and selective coding. Constant comparative analysis was applied to identify patterns, relationships, and conceptual categories. The rigor and credibility of findings were ensured through memo writing, continuous comparison, participant validation, and theoretical integration. The final analytical outcome was the construction of a paradigmatic model linking causal conditions, contextual and intervening factors, strategies, the central phenomenon, and resulting organizational outcomes.Findings: The results indicated that career plateauing among accountants is primarily driven by organizational financial pressures, blocked promotion pathways, and declining intrinsic motivation. Contextual conditions such as inflexible hierarchical structures, passive organizational culture, and weaknesses in professional training systems were found to sustain plateau experiences. Intervening factors—including financial technology transformations, complex regulatory changes, and conflicting stakeholder expectations—intensified professional stagnation while simultaneously creating opportunities for role transformation. The core phenomenon emerged as structural career plateauing accompanied by devaluation of professional expertise. Strategic responses such as multidimensional competency development, targeted professional networking, and organizational role redefinition were associated with positive outcomes including professional stabilization, improved organizational performance, and broader systemic impacts on the insurance sector.Conclusion: The study demonstrates that career plateauing is a multidimensional organizational phenomenon rather than an individual limitation and that strategic managerial interventions focused on competency development, professional recognition, and structural redesign can transform plateau conditions into opportunities for professional consolidation, organizational effectiveness, and institutional sustainability.